The performance of socially responsible equity mutual funds: Evidence from Sweden. (30th October 2017) - Leite, Carlos; Cortez, Maria Ceu; Silva, Florinda; Adcock, Christopher
Abstract : This paper presents a comprehensive analysis of socially responsible (SR) funds in Sweden by assessing fund managers' abilities and performances across different market states. These issues are analyzed at the aggregate and individual fund levels. The paper also presents several new statistical tests that allow more precise inferences about differences in performance and the variability in fund returns arising from different benchmarks. In general, SR and conventional funds perform similarly to the market. At the aggregate level, SR funds investing in Sweden and Europe perform similarly to conventional funds, while those investing globally tend to underperform. This underperformance seems to be linked with poor selectivity abilities of global SR fund managers. For individual funds, the performance of both types of funds is more similar. Most funds perform similarly in crisis periods compared to non‐crisis periods. Overall, our results are consistent with a mature market for SR investing and support the view that the similar performance of SR and conventional funds is associated with the mainstreaming of SR investment in Sweden. These findings encourage SR investing both by socially conscious investors, who wish to align their social values with their investment decisions, as well as by conventional investors, who will not be penalized by investing in these funds. We also call attention to the difficulties investors face when trying to identify funds with high social standards, considering that there is scarce information on the extent to which each fund (SR or conventional) holds stocks that comply with ethical and social criteria.